ALBUMIN KREATININ PENDERITA HIPERTENSI HAKIKI (ESENSIAL) - T. Wongso; Dewi LS; Z. Lubis (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
Increasing of urine albumin excretion in hypertension patient is early sign of renal excretion disorder. Increasing of urine albuminexcretion could not detect with conventional methods, but with more sensitive methods, one of them is examined ratio of urine albuminand urine creatinine (ACR). Knowing ACR rate in essential hypertension. This research was done by cross sectional with consecutivesampling of hypertension patient with JNC VII 2003 criteria. Research used quantitative urine albumin with Albumin Tina QuantMethods draught Immunoturbidinetry. The urine creatinine was analyzed with Jaffe Methods using Roche Hitachi 902. From 25 peopleof hypertension group found ACR < 30 mg/g amount 16 people and ACR rate 30–300 mg/g amount 9 people. Mean while from 22people of non hypertension, all had ACR < 30 mg/g. In this research also found strong correlation between ACR with hypertension,diastolic and systolic blood pressure. It was found that ACR rate of hypertension group was higher than the non hypertension group. Itwas also found a strong relation between ACR with hypertension, systolic and blood diastolic pressure.